Adaptation of climate change and environmental pollution in Cirebon’s coastal community - Mulyadi Asep (E3S Web of Conferences)
Climate change and environmental pollution are interrelated global phenomena. Communities whose lives depend on natural resources have felt many negative impacts from both. Coastal communities, which mostly depend on the capture fisheries, are a vulnerable group to these threats. The study aims to reveal the adaptation of coastal communities in Cirebon, Indonesia to facing climate change and environmental pollution. This research is located in Gebang Cirebon Regency. Data were obtained from field observations and unstructured interviews which were synthesized to know their adaptive behaviour. We found the adaptation of coastal communities through non-environmentally fishing gears, expansion of fishing areas, burden of debt and capital, not optimal fisherman regeneration, and changes in occupation. Despite changes in mindset, attitude, and behaviour, these adaptations have the potential to threaten a regional and national economy because the fisheries sector is the main contributor of gross domestic product. Declining yield catches and the desire to obtain high economic benefits quickly without paying attention to sustainability, are also the main driving factors for the emergence of maladaptive behaviour in coastal communities. Without serious attention, climate change and environmental pollution will trigger socio-economic impacts that are worse than COVID-19 pandemic.